Methanol oxidation on stoichiometric and oxygen-rich RuO2(110). Issue 29 (12th July 2017) - Rai, Rahul; Weaver, Jason F.
Abstract : We used temperature-programmed reaction spectroscopy (TPRS) to investigate the adsorption and oxidation of methanol on stoichiometric and O-rich RuO2 (110) surfaces. Abstract : We used temperature-programmed reaction spectroscopy (TPRS) to investigate the adsorption and oxidation of methanol on stoichiometric and O-rich RuO2 (110) surfaces. We find that the complete oxidation of CH3 OH is strongly preferred on stoichiometric RuO2 (110) during TPRS for initial CH3 OH coverages below ∼0.33 ML (monolayer), and that partial oxidation to mainly CH2 O becomes increasingly favored with increasing CH3 OH coverage from 0.33 to 1.0 ML. We present evidence that an adsorbed CH2 O2 species serves as the key intermediate to complete oxidation and that CH2 O2 formation is intrinsically facile but becomes limited by the availability of bridging O-atoms on stoichiometric RuO2 (110) at initial CH3 OH coverages above 0.33 ML. We show that methanol molecules adsorbed in excess of 0.33 ML dehydrogenate to mainly CH2 O and desorb during TPRS, with adsorbed CH3 O groups mediating the evolution of both CH2 O and CH3 OH. We find that O-rich RuO2 (110) surfaces are also highly active toward methanol oxidation and that selectivity toward the complete oxidation of methanol increases markedly with increasing coverage of on-top O-atoms (Oot ) on RuO2 (110). Our results demonstrate that CH3 OH species adsorbed within Oot -rich domains react efficiently during TPRS, in parallel with reaction of CH3 OH adsorbed initially on cus-Ru sites. The data suggests that the facile hydrogenation of Oot atoms and the resulting desorption of H2 O at low-temperature (<∼400 K) provides an efficient pathway for restoring reactive O-atoms and thereby promoting complete oxidation of methanol on the O-rich RuO2 (110) surface.